2007
DOI: 10.1055/s-2007-977448
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Naphthalenide Induced Reductive Selenenylation of α-Cyano Ketones: A Regiocontrolled Process for α-Phenylseleno Ketones and One-Pot Conversion into Enone System

Abstract: An efficient procedure for the regiocontrolled synthesis of a-phenylseleno ketones has been developed, making use of the lithium naphthalenide induced reductive selenenylation of the a-cyano ketone system as a key operation. Moreover, seleno ketones thus generated in situ, upon subsequent treatment with hydrogen peroxide and acetic acid, could be further converted into the corresponding enones with a high degree of regioselectivity, presumably due to the lithium salt mediated selenoxide syn-elimination process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Moreover, a-phenylseleno thus formed without isolation upon subsequent treatment with hydrogen peroxide and acetic acid, could be further converted into the corresponding a,b-unsaturated ketones with high regioselectivity. 13 (D) Reductive Cleavage of a,b-Epoxy Ketones: LN is also used as a mild and efficient reagent for the reductive of a,b-epoxy ketones to give the corresponding b-hydroxy ketones. 14 (E) Reductive Elimination of Epoxy Mesylates: Wu et al have found that LN can serve as a mild reducing agent for reductive elimination of epoxy mesylates into the transpositioned allylic alcohol.…”
Section: Scheme 1 Abstractsmentioning
confidence: 99%
“…Moreover, a-phenylseleno thus formed without isolation upon subsequent treatment with hydrogen peroxide and acetic acid, could be further converted into the corresponding a,b-unsaturated ketones with high regioselectivity. 13 (D) Reductive Cleavage of a,b-Epoxy Ketones: LN is also used as a mild and efficient reagent for the reductive of a,b-epoxy ketones to give the corresponding b-hydroxy ketones. 14 (E) Reductive Elimination of Epoxy Mesylates: Wu et al have found that LN can serve as a mild reducing agent for reductive elimination of epoxy mesylates into the transpositioned allylic alcohol.…”
Section: Scheme 1 Abstractsmentioning
confidence: 99%
“…In principle, the corresponding -phenylseleno alkenones could also serve as effective dienophiles for Diels-Alder reaction [24], providing facile access to -phenylseleno ketones, which might be useful in the preparation of various , -unsaturated cyclic ketones or have potential to serve as anti-cancer and anti-inflammatory agents [25]. Initial attempts to carry out Diels-Alder reactions with these dienophiles under thermal conditions were fruitless.…”
Section: -Phenylthio/phenylselenenyl/ptolylsulphinyl Cycloalkenones Amentioning
confidence: 99%
“…7 We have been working on devising more powerful and versatile methods for the preparation of a-(phenylselanyl) carbonyl compounds, and have recently reported a highly efficient procedure for the preparation of a-(phenylselanyl) ketones from the corresponding a-cyano ketones. 8 Our approach is based on the reductive decyanation of acyano ketones: reduction with lithium naphthalenide (LN) is followed by the rapid one-pot selenenylation of the resulting enolates with phenylselenenyl bromide (PhSeBr); this gives the corresponding a-(phenylselanyl) ketones with the overall replacement of the cyano group by a phenylselanyl group. Through this protocol, a great variety of a-cyano ketones have been efficiently converted into the corresponding a-(phenylselanyl) ketones with complete control over the regiochemistry.…”
mentioning
confidence: 99%
“…Our recent studies on some addition and cyclization reactions involving carbon-centered radicals resulting from C-Se bond cleavage required the efficient generation of highly substituted a-(phenylselanyl)acetates with a broad structural diversity. On the basis of our previous experiences, 8 we envisaged that a process involving the reductive selenenylation of a-cyano esters might lead to an attractive method. Our strategy consisted of first introducing the selected alkyl groups to the a-position of cyanoacetate 6, to provide a,a-dialkyl-a-cyanoacetates 7 (Scheme 2), which would then be subjected to reductive selenenylation, thus giving the desired products 1 by intentional control of the substitutions at the quaternary carbon center (Scheme 2).…”
mentioning
confidence: 99%